Pergeseran Penerjemahan Pada Teks Terjemahan Lagu Berbahasa Jepang Yang Dibawakan Oleh Andi Adinata - Fauzah, Nunik Nur Rahmi; Hidayati, Yanti; Gumelar, Wawan Agung (Universitas Diponegoro, 2023)
(Translation Shift on Songs from Japan Into Indonesia by Andi Adinata) The purpose of this study was to find out which words experienced a translation shift and to describe the translation shift in the text of the Japanese song translation performed by Andi Adinata. The data is the translation of the lyrics of the song which is sourced from the song entitled 'Harusnya Aku' from Armada, 'Surat Cinta Untuk Starla' from Virgoun, 'Ceria' from J-Rocks, 'Munajat Cinta' from The Rock, 'Semua Tentang Kita' from Peterpan and 'Bukti' from Virgoun. The method is a qualitative descriptive method. Data collection was done by observing and note-taking methods. Data analysis was carried out using the translational equivalent method and the determining element sorting technique (PUP). In this study found as many as 45 data. Words that experienced a translation shift were 42 words and a total of 83 translation shifts, namely level shifts totaling 4 shifts and category shifts totaling 79 shifts. Of the 79 category shifts, there are 3 structure shifts, 25 words class shifts, 14 unit shifts and 37 intrasystem shifts. This study concludes that there are two types of translation shifts, namely level shifts and category shifts and there are four types of category shifts, namely structure shifts, class shifts, unit shifts and intrasystem shifts. <a href=